MULTIKULTURAL PERSPEKTIF SOSIOLOGIS - Nofal Liata; Khairil Fazal (Prodi Studi Agama-Agama, 2021)
This study discusses the concept of a multicultural society in a sociological perspective, where the Indonesian state as a gathering place for various ethnic groups, nations, religions and beliefs in its history has provided valuable lessons. There are times when diversity in Indonesia creates conflict, but in other places there is also the diversity that is owned by the Indonesian people as a source of strength to keep each other from being crushed by the progress of the times. Understanding multiculturalism is not something that must be owned by intellectuals or those from community leaders only, but all levels, layers, and lines of society become a necessity for the importance of understanding this multiculturalism. Because at this time the reality is that Indonesian people in general are very vulnerable to disaster due to SARA (ethnic, religion, race, and inter-group) issues that are blown by electronic media. In order to prevent